Ruthenium Porphyrin Compounds for Photodynamic Therapy of Cancer - Schmitt, Frederic; Govindaswamy, Padavattan; Süss-Fink, Georg; Ang, Wee Han; Dyson, Paul J.; Juillerat-Jeanneret, Lucienne; Therrien, Bruno (My University, 2008)
Five 5,10,15,20-tetra(4-pyridyl)porphyrin (TPP) areneruthenium(II) derivs., a p-cymeneosmium, a pentamethylcyclopentadienyliridium and a pentamethylcyclopentadienylrhodium analog were prepd. and characterized as potential photosensitizing chemotherapeutic agents. The dinuclear areneruthenium complexes [Ru(?6-arene)(?-Cl)Cl]2 (arene = C6H6, C6H5CH3, p-iPrC6H4Me, C6Me6, and 1,4-C6H4(COOEt)2) react with TPP in MeOH to give the corresponding tetranuclear complexes [Ru4(?6-arene)4(TPP)Cl8] (arene = C6H6 (1, 56% yield), C6H5CH3 (2, 70%), p-iPrC6H4Me (3, 70%), C6Me6 (4, 79%), 1,4-C6H4(COOEt)2 (5, 73%)). The dinuclear p-cymeneosmium complex [Os(?6-p-iPrC6H4Me)(?-Cl)Cl]2 reacts with TPP to form the tetranuclear areneosmium complex [Os4(?6-p-iPrC6H4Me)4(TPP)Cl8] (6) in 47% yield. The isoelectronic Rh and Ir pentamethylcyclopentadienyl derivs. [Rh4(?5-C3Me5)4(TPP)Cl8] (7, 73%) and [Ir4(?5-C3Me5)4(TPP)Cl8] (8, 83%) were obtained in MeOH from the reaction of [M(?5-C5Me5)(?-Cl)Cl]2 (M = Rh, Ir) with TPP. The mol. structures of 4 and 7 were detd. by x-ray crystallog. The biol. effects of all these derivs. were assessed on human melanoma tumor cells, and their cellular uptake and intracellular localization were detd. All mols., except the Rh complex which was not cytotoxic, demonstrated comparable cytotoxicity in the absence of laser irradn. The Ru complexes exhibited excellent phototoxicities toward melanoma cells when exposed to laser light at 652 nm. Cellular uptake and localization microscopy studies of [Ru4(?6-C6H5CH3)4(TPP)Cl8] and [Rh4(?5-C5Me5)4(TPP)Cl8] revealed that they accumulated in the melanoma cell cytoplasm in granular structures different from lysosomes. The fluorescent porphyrin moiety and the metal component were localized in similar structures within the cells. Thus, the porphyrin areneruthenium(II) derivs. represent a promising new class of organometallic photosensitizers able to combine chemotherapeutic activity with photodynamic therapeutic treatment of cancer. [on SciFinder(R)]
Keywords: dinuclear areneruthenium areneosmium cyclopentadienylrhodium cyclopentadienyliridium reaction tetrapyridylporphyrin; crystal mol structure tetranuclear areneruthenium cyclopentadienylrhodium porphyrin complex prepn; areneruthenium cyclopentadienylrhodium cyclopentadienyliridium areneosmium porphyrin prepn photodynamic therapy melanoma